2002
DOI: 10.1001/archinte.162.6.682
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Antibiotic Delivery and Appropriate Antibiotic Selection Reduce Length of Hospital Stay of Patients With Community-Acquired Pneumonia

Abstract: Unlike clinical and demographic variables, process-of-care variables are modifiable and amenable to quality improvement. We observed that rapid antibiotic initiation and appropriate antibiotic selection in the emergency department have a statistically significant association with shorter LOS. These findings suggest quality improvement targeted at these processes of care may improve resource utilization and reduce LOS for patients with community-acquired pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
1
16

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(158 citation statements)
references
References 19 publications
4
135
1
16
Order By: Relevance
“…Though the literature has not definitively correlated a delay in antibiotics to adverse outcomes in children with FN, such an association has been shown in other clinical situations [6]. Battleman et al [6] showed a correlation between the timing of antibiotic administration and the length of stay in hospital in adults with community-acquired pneumonia, suggesting that antibiotic delay may lead to increased morbidity and financial expenditure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the literature has not definitively correlated a delay in antibiotics to adverse outcomes in children with FN, such an association has been shown in other clinical situations [6]. Battleman et al [6] showed a correlation between the timing of antibiotic administration and the length of stay in hospital in adults with community-acquired pneumonia, suggesting that antibiotic delay may lead to increased morbidity and financial expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Battleman et al [6] showed a correlation between the timing of antibiotic administration and the length of stay in hospital in adults with community-acquired pneumonia, suggesting that antibiotic delay may lead to increased morbidity and financial expenditure. Rivers et al [7] showed better outcomes and improved survival with early goal-directed therapy for adults with severe sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…La administración de la primera dosis de antibiótico se debiera realizar en Urgencias lo antes posible (8,13,14), una vez realizada la historia clínica, exploración, radiología de tórax, muestras analíticas, toma de hemocultivos y cultivos pertinentes (esputo, orina, etc. ), y antes de ser enviado a planta médica que demora el tratamiento.…”
Section: Resultsunclassified
“…3,5 Appropriate and timely antibiotic treatment of pneumonia reduces the risk of complications, helps curb the development of antibiotic resistance, decreases health care costs, and reduces morbidity and mortality. [6][7][8][9][10] Inappropriate empiric antibiotic therapy is associated with an increased risk of death, prolonged length of hospital stay, higher rates of clinical failure, and more frequent readmission to hospital. [11][12][13][14] Changing therapy once culture results are available may not reduce this risk; therefore, appropriate empiric therapy is essential for an optimal outcome.…”
Section: Introductionmentioning
confidence: 99%